The Future of Crop Improvement in Sweetpotato: Merging Traditional and Genomic-Assisted Breeding Methods - Oloka, B.; Da Silva, C.C.; Azevedo, C.F.; Unzimai, I.V.; Yada, B.; Grüneberg, W.J.; Andrade, M.I.; Pecota, K.V.; Silva Pereira, G. da; Yencho, G.C. (2024)
Crop improvement in sweetpotato has progressed slowly in many parts of the world largely due to its significant genetic complexity arising from its large autohexaploid genome, high heterozygosity, and self and cross-incompatibilities. New breeding tools have been developed to better understand this crop and its important agronomic and culinary traits. These tools and their application are reviewed here, and the path forward has been proposed. By incorporating these new genomic tools into breeding programs routinely alongside the traditional methods, crop improvement can be accelerated, leading to the delivery of clones with better genetics to farmers more quickly. This integration of genomics could propel sweetpotato into a new era, ultimately enhancing its productivity and profitability, which is crucial given the growing global population.